Determinants of Establishing a Tourist Environment Towards Distinctive Entrepreneurship on Pedicab Transportation - PANJAITAN, Mangasa (Journal of Environmental Management and Tourism; Vol 9 No 8 (2018): JEMT Volume IX Issue 8(32) Winter 2018, 2019)
The purpose of this research was Determinants of Establishing a Tourist Environment towards Distinctive Entrepreneurship on Pedicab Transportation. The Purpose of this research is knowing Determinants of Establishing a Tourist Environment towards Distinctive Entrepreneurship on Pedicab Transportation. It was motorcycles who produced from BSA of United Kingdom-made 350-500 cc.  The problem is the tendency of lost their potential customers because of the competition with the online transportation that it grown rapidly.  A sample of 97 respondents from the people was considered for this research. Limeshow sampling technique was used to select customers were purposively sampled.  The study concluded that psychological factors have a positive effect but not significant (motivated, perception) and attitude and behavior have significant, in other hand learning has a negative effect on consumer’s decision in Pedicab Transportation.